1993
DOI: 10.1111/j.1365-3148.1993.tb00116.x
|View full text |Cite
|
Sign up to set email alerts
|

An evaluation of a gel technique for antibody screening compared with a conventional tube method

Abstract: Summary. An antihuman globulin (AHG) gel centrifugation technique (AHG gel test) employing microtubes (DiaMed®) has been compared for sensitivity in detection of unexpected antibodies with a saline indirect antiglobulin test (SIAT) which uses a cell‐to‐serum ratio between 1:120 and 1:200 and provides positive reactions at a concentration of a standard anti‐D of 2 ng/mL (0·01 IU/ml) or less. For most antibodies examined the AHG gel test was slightly less sensitive than the SIAT but both methods were capable of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
17
0

Year Published

1996
1996
2013
2013

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(22 citation statements)
references
References 11 publications
(7 reference statements)
5
17
0
Order By: Relevance
“…(1992) who found DiaMed‐ID to be less sensitive than LISS‐IAT in detecting weak anti‐Fy b , anti‐Jk a and anti‐S. In an evaluation conducted by Pinkerton et al . (1993) of 39 sera, comparing DiaMed‐ID with NISS‐IAT (serum to cell ratio of between 120 : 1 and 200 : 1), several examples of anti‐Jk a required additional complement before they were detectable by DiaMed‐ID, and detectable examples gave a lower titre with this technology.…”
Section: Discussionsupporting
confidence: 72%
“…(1992) who found DiaMed‐ID to be less sensitive than LISS‐IAT in detecting weak anti‐Fy b , anti‐Jk a and anti‐S. In an evaluation conducted by Pinkerton et al . (1993) of 39 sera, comparing DiaMed‐ID with NISS‐IAT (serum to cell ratio of between 120 : 1 and 200 : 1), several examples of anti‐Jk a required additional complement before they were detectable by DiaMed‐ID, and detectable examples gave a lower titre with this technology.…”
Section: Discussionsupporting
confidence: 72%
“…Some workers found a higher sensitivity in the microtube column systems compared to the tube test (Bromilow et al , 1991; Voak, 1999; Weisbach et al , 1999). However, other investigators found the microtube column systems to be slightly less sensitive than the tube test (Phillips et al , 1992; Voak, 1992; Pinkerton et al , 1993). This discrepancy is most likely due to different characteristics of tube tests, which were compared to the gel test (Issitt & Anstee, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…This discrepancy is most likely due to different characteristics of tube tests, which were compared to the gel test (Issitt & Anstee, 1998). For example, Pinkerton et al (1993) used a tube saline IAT with a comparably high ratio of serum to red cells between 120 : 1 and 200 : 1 combined with a microscopic confirmation of negative results. The new methods have important advantages compared to the tube test: they are less susceptible to handling errors, reading of results can be repeated, and, most important, the new methods can be performed automatically.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Dal antigen investigators utilized a gel technology in conjunction with a standard tube technology for crossmatching and reported agreement of both methods 11 . In human medicine the gel test is comparable to the tube assay for both the indirect and direct antiglobulin tests 23–26 . There are currently 2 commercially available gel tests for canine and feline crossmatching: one manufactured by DiaMed and one manufactured by DMS Laboratories e,f (Figure 4).…”
Section: Crossmatching Methodsmentioning
confidence: 99%